Continuous Isoprene Measurements in a UK Temperate Forest for a Whole Growing Season: Effects of Drought Stress During the 2018 Heatwave. Issue 15 (29th July 2020) - Ferracci, Valerio; Bolas, Conor G.; Freshwater, Ray A.; Staniaszek, Zosia; King, Thomas; Jaars, Kerneels; Otu‐Larbi, Frederick; Beale, John; Malhi, Yadvinder; Waine, Toby William; Jones, Roderic L.; Ashworth, Kirsti; et al.
Abstract: Isoprene concentrations were measured at four heights below, within, and above the forest canopy in Wytham Woods (United Kingdom) throughout the summer of 2018 using custom‐built gas chromatographs (the iDirac). These observations were complemented with selected ancillary variables, including air temperature, photosynthetically active radiation, occasional leaf gas exchange measurements, and satellite retrievals of normalized difference vegetation and water indices. The campaign overlapped with a long and uninterrupted heatwave accompanied by moderate drought. Peak isoprene concentrations during the heatwave‐drought were up to a factor of 4 higher than those before or after. Higher temperatures during the heatwave could not account for all the observed isoprene; the enhanced abundances correlated with drought stress. Leaf‐level emissions confirmed this and also included compounds associated with ecosystem stress. This work highlights that a more in‐depth understanding of the effects of drought stress is required to better characterize isoprene emissions. Plain Language Summary: Plants emit a number of volatile organic compounds into the atmosphere as a response to environmental stimuli such as temperature and incoming sunlight. Once emitted, these compounds undergo chemical processes that can affect local air quality (for instance, contributing to the formation of pollutants such as ground‐level ozone) and climate (by contributing to the formation of aerosol particles). Numerical models have been developed to successfully simulate volatile emissions under most environmental conditions. However, one notable exception is during extreme weather events such as heatwaves and droughts, where current models appear inadequate. In this paper, we present a unique data set consisting of continuous measurements of isoprene, the main volatile emission from vegetation, during the summer of 2018 in a UK temperate forest. A prolonged heatwave and drought affected the United Kingdom that summer. We report unusually high levels of isoprene and show that higher temperatures during the heatwave cannot account for all the observed isoprene. Our analysis shows that ecosystem stress brought about by moderate drought correlates with the enhanced isoprene. This work enables an improved description of isoprene emissions under extreme events (droughts) that are predicted to become more frequent in the near future as a consequence of global change. Key Points: Isoprene concentrations were monitored for a whole growing season in a temperate forest in the United Kingdom before, during, and after the 2018 heatwave Isoprene abundances during the heatwave increased by up to 400%, and stress‐related sesquiterpenes were observed during the heatwave Higher temperatures in the heatwave cannot account for all the enhanced isoprene abundances, which correlate to drought stress